Understanding innovation process within an interactive social network: Empirical insights from maize innovations in southern Ghana - Nana Afranaa Kwapong; Daniel Adu Ankrah (Cogent Social Sciences)
Agricultural innovations propel improvement in agricultural productivity. Even though, the related literature largely reports low adoption of innovations, the literature deficiently accounts for the complexities and the interactive social contexts that embed innovation processes. In addressing the lacuna, it remains imperative to understand the complexities of the innovation process. This study assesses the factors influencing the intricate innovation processes toward the uptake of maize innovations among smallholder farmers in Ghana. The study relied on focus group discussions, observations, and individual in-depth interviews with thirty maize farmers in Kintampo District and Wenchi Municipal Assembly in Ghana. Content analysis was used to analyze the qualitative information. The findings show many instances of learning, knowledge transfer, and uptake of practices among farmers during innovation processes. We find adaptations to existing farm practices, and local contexts. With unintended outcomes which appear useful for learning and co-learning in the innovation ecosystem. The innovation processes are shaped by farmers characteristics and personal goals, trialability of technology, social network, relative advantage of the technology, access to information and extension services, and sociocultural conditions in the external environment. The farmer field schools, and field days constitute important conduits in promoting increased maize innovations uptake among farmers. We suggest that, in understanding adoption, focus should be paid to the complexities in the innovation processes reckoning that it is embedded in an interactive social network, with many instances of learning, co-learning, knowledge transfer, contestations, and negotiations. This should guide policy decisions to better inform the design of programme interventions.